Effect of Omega-3 Supplementation on Quality of Life in Patients with Psoriasis: A Digital Survey-based Study - Anders D. Andersen; Alexander Almegaard; Anders Nikolai Schultz; John Robert Zibert (Medical Journals Sweden, 2019)
Abstract is missing (short communication)